Avoidance behavior in chronic pain research: A cold case revisited. (January 2015) - Volders, Stéphanie; Boddez, Yannick; De Peuter, Steven; Meulders, Ann; Vlaeyen, Johan W.S.
Abstract: In chronic musculoskeletal pain, avoidance behavior is a prominent behavioral characteristic that can manifest itself in various ways. It is also considered a crucial component in the development and maintenance of chronic pain-related disability, supposedly fueled by pain-related fear and catastrophic beliefs. Despite the frequent occurrence of avoidance behavior and its potential impact on quality of life, relatively little research has been dedicated to the nature of avoidance in chronic pain and its assessment, leaving its underlying mechanisms poorly understood. In the current paper, we stipulate some of the existing parallels between chronic pain research and more basic fear and anxiety research inspired by modern learning theories. After a brief introduction, we discuss avoidance theories that are likely apt to be applied to chronic pain, including avoidance as a response that can affect fear responding, and the role of avoidant decision making and motivational context. Finally, we will outline how these theories may impact clinical treatment. Highlights: Avoidance behavior is a crucial factor in chronic pain-related disability. Avoidance behavior in chronic pain is poorly understood and vaguely conceptualized. General anxiety theories have common elements with fear-avoidance models of pain. General anxiety-learning theories do suggest why and how avoidance may be disabling. Adopting a learning theory perspective could improve understanding of avoidance.